Aluminum-based metal material with chemical conversion coating film, chemical conversion treatment liquid for aluminum-based metal material, and surface treatment method for aluminum-based metal material
The chemical conversion treatment liquid for aluminum-based metal materials, incorporating zirconium, titanium, or vanadium, trivalent chromium, a polymer with a carbonyl group, and a fluorine-containing compound, addresses the challenge of achieving corrosion resistance in acidic and Cu-containing environments, while maintaining performance in neutral conditions.
Patent Information
- Application Number
- JP2023178485
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-28
AI Technical Summary
Existing chemical conversion treatment liquids for aluminum-based metal materials struggle to form a chemical conversion film with excellent corrosion resistance in acidic environments and those containing Cu, despite performing well in neutral environments.
A chemical conversion treatment liquid containing specific amounts of zirconium, titanium, or vanadium, trivalent chromium, a polymer with a carbonyl group, and a fluorine-containing compound, applied to aluminum-based metal materials to form a conversion coating with optimized mass ratios and composition.
The solution achieves excellent corrosion resistance for aluminum-based metal materials not only in neutral environments but also in acidic environments and those containing Cu, through the formation of a robust chemical conversion film.
Smart Images

Figure 2025068520000005 
Figure 2025068520000001 
Figure 2025068520000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum-based metallic material with a chemical conversion coating, a chemical conversion treatment solution for an aluminum-based metallic material, and a method for surface treatment of an aluminum-based metallic material. [Background technology]
[0002] Conventionally, chemical conversion treatment solutions containing trivalent chromium for metal materials have been developed for use in a wide range of fields, including aircraft materials, building materials, and automobile parts.
[0003] For example, Patent Document 1 discloses a chemical conversion treatment liquid for metallic materials that contains component (A) consisting of a water-soluble trivalent chromium compound, component (B) consisting of at least one compound selected from a water-soluble titanium compound and a water-soluble zirconium compound, component (C) consisting of a water-soluble nitrate compound, component (D) consisting of a water-soluble aluminum compound, and component (E) consisting of a fluorine compound.
[0004] Patent Document 2 discloses a chemical conversion treatment liquid for metallic materials that contains predetermined amounts of a specific trivalent chromium compound, a specific zirconium compound, and a specific dicarboxylic acid compound.
[0005] Patent Document 3 discloses a chemical conversion treatment liquid for metallic materials that contains predetermined amounts of a specific trivalent chromium compound, a specific zirconium compound, a specific phenol compound, and a fluorine-containing compound. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2006-328501 A [Patent Document 2] JP 2006-316334 A [Patent Document 3] International Publication No. 2019 / 131436 Summary of the Invention [Problem to be solved by the invention]
[0007] However, while the chemical conversion treatment solutions for metal materials according to Patent Documents 1 to 3 are capable of forming a chemical conversion film having excellent corrosion resistance in a neutral environment on an aluminum-based metal material, it is difficult to form a chemical conversion film having excellent corrosion resistance even in an acidic environment and an environment containing Cu.
[0008] In view of the above circumstances, in one embodiment, the present invention aims to provide an aluminum-based metal material with a chemical conversion coating that has excellent corrosion resistance not only in a neutral environment but also in an acidic environment and an environment containing Cu. In another embodiment, the present invention aims to provide a chemical conversion treatment liquid for an aluminum-based metal material that is suitable for obtaining the aluminum-based metal material with a chemical conversion coating. In yet another embodiment, the present invention aims to provide a method for surface treatment of an aluminum-based metal material using the chemical conversion treatment liquid for an aluminum-based metal material. [Means for solving the problem]
[0009] As a result of intensive research, the inventors have found that the above-mentioned problems can be solved by forming a chemical conversion coating containing predetermined amounts of predetermined components on the surface of an aluminum-based metallic material, and have thus completed the present invention.
[0010] That is, the present invention is exemplified as follows. [Aspect 1] At least one metal element (A) selected from the group consisting of Zr, Ti and V is applied to the surface of an aluminum-based metal material at a concentration of 1 mg / m 2 ~160mg / m 2 and 5 to 50 mg / m of non-hexavalent Cr element (B). 2 and C element 6 to 100 mg / m 2 and wherein the mass ratio (A / B) of the metal element (A) to the Cr element (B) that is not hexavalent Cr is 1.45 to 5.0, and the mass ratio (C / B) of the C element to the Cr element (B) that is not hexavalent Cr is 0.15 to 7.2. [Aspect 2] 2. The aluminum-based metal material with a chemical conversion coating according to embodiment 1, wherein the C element in the chemical conversion coating is derived from a polymer having a carbonyl group. [Aspect 3] 3. The aluminum-based metallic material with a chemical conversion coating according to aspect 1 or 2, wherein the chemical conversion coating contains an F element. [Aspect 4] In the emission intensity analysis using a Marcus-type high-frequency glow discharge optical emission surface analyzer (GD-OES), the depth range from the outermost surface to within 20 nm is defined as the surface side, and the depth range from the depth at which the Al intensity first reaches 5 times the average value of the Al intensity in the depth range from the outermost surface to 5 nm is defined as the substrate side. The aluminum-based metal material with a chemical conversion coating according to any one of aspects 1 to 3, wherein the C element and the O element show maximum strength on the surface layer side, and at least one element selected from the metal element (A) and the Cr element (B) that is not hexavalent Cr shows maximum strength on the substrate side. [Aspect 5] A chemical conversion treatment liquid for aluminum-based metallic materials, comprising: at least one metal compound (a) selected from the group consisting of zirconium compounds, titanium compounds, and vanadium compounds; a trivalent chromium compound (b); a polymer (C) having a carbonyl group; and a fluorine-containing compound (D). [Aspect 6] A chemical conversion treatment solution for aluminum-based metallic materials according to aspect 5, wherein a mass ratio (A / B) of at least one metal element (A) selected from the group consisting of Zr, Ti, and V to a Cr element (B) that is not hexavalent Cr is 0.6 to 7.0, and a mass ratio (C / B) of a C element to the Cr element (B) that is not hexavalent Cr is 0.5 to 20. [Aspect 7] 7. The chemical conversion treatment liquid for aluminum-based metallic materials according to aspect 5 or 6, wherein a mass ratio (X / Y) of the mass (X) of the polymer (C) having a carbonyl group to the total mass (Y) of Zr, Ti, V and Cr is 0.50 to 2.80. [Aspect 8] A step (i) of contacting an aluminum-based metallic material with the chemical conversion treatment solution for an aluminum-based metallic material according to any one of aspects 5 to 7 for 60 seconds or more; After the step (i), a step (ii) of washing the aluminum-based metallic material with water; The surface treatment method of the aluminum-based metal material includes the steps of: [Aspect 9] 9. The method for surface treatment of an aluminum-based metallic material according to embodiment 8, wherein in the step (i), the aluminum-based metallic material is brought into contact with the chemical conversion treatment solution for aluminum-based metallic materials for a period of 60 to 600 seconds. Effect of the Invention
[0011] According to one embodiment of the present invention, an aluminum-based metal material with a chemical conversion coating can be obtained, which has excellent corrosion resistance not only in a neutral environment but also in an acidic environment and an environment containing Cu. According to another embodiment of the present invention, a chemical conversion treatment liquid for an aluminum-based metal material suitable for obtaining the aluminum-based metal material with a chemical conversion coating can be obtained. According to yet another embodiment of the present invention, a surface treatment method for an aluminum-based metal material using the chemical conversion treatment liquid for an aluminum-based metal material can be obtained. [Brief description of the drawings]
[0012] [Figure 1] This is an example of the emission intensity profile of each element obtained when performing depth profiling using GD-OES. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, embodiments of the present invention will be described. Note that in the present invention, the description of "X to Y" indicating a numerical range means "not less than X and not more than Y".
[0014] <<1. Aluminum-based metal materials with chemical conversion coating>> (Aluminum-based metal materials) The aluminum-based metal material according to an embodiment of the present invention is not particularly limited, and may be a pure aluminum material, an aluminum alloy material, or the like. Examples of the aluminum alloy material include Al-Cu, Al-Si, Al-Mg, Al-Zn, Al-Si-Cu, Al-Si-Mg, Al-Co-Cu, Al-Mn-Mg, Al-Mn-Fe, and Al-Mn-Zn-Fe-Mg materials. The aluminum-based metal material may be used alone or as a composite material in combination with other metals, ceramics, or the like.
[0015] (At least one metal element (A) selected from the group consisting of Zr, Ti, and V) A chemical conversion coating according to one embodiment of the present invention contains at least one metal element (A) selected from the group consisting of Zr (zirconium), Ti (titanium), and V (vanadium). The content of metal element (A) in the chemical conversion film is 1 mg / m 2 ~160mg / m 2 and preferably 5 mg / m 2 ~160mg / m 2 and more preferably 10 mg / m 2 ~160mg / m 2 and even more preferably 20 mg / m 2 ~160mg / m 2 When two or more metal elements (A) are contained in the chemical conversion coating, the total content of the metal elements (A) is the content of the metal element (A). 2 If it is lower than this, sufficient corrosion resistance cannot be obtained, and the maximum is 160 mg / m 2 If it is higher, the cost increases.
[0016] The compound form of the metal element (A) contained in the chemical conversion coating according to one embodiment of the present invention is not particularly limited. The metal element (A) in the chemical conversion coating may be a metal compound (a) contained in the chemical conversion treatment liquid for aluminum-based metallic materials described below that is directly incorporated into the chemical conversion coating, or the metal compound (a) may be converted into another compound form (such as an oxide) by a chemical conversion reaction with the aluminum-based metallic material and then incorporated.
[0017] (Cr element (B) that is not hexavalent Cr) The chemical conversion coating according to one embodiment of the present invention contains a Cr (chromium) element (B) that is not hexavalent Cr. The content of non-hexavalent Cr element (B) in the chemical conversion coating is 5 to 50 mg / m 2 and preferably 10 to 50 mg / m 2 and more preferably 15 to 50 mg / m 2 and even more preferably 20 to 50 mg / m 2 The content of non-hexavalent Cr element (B) is 5 mg / m 2 If it is lower than this, sufficient corrosion resistance cannot be obtained, and 50 mg / m 2 If it is higher, the cost increases.
[0018] The compound form of the Cr element (B) other than hexavalent Cr contained in the chemical conversion film according to one embodiment of the present invention is not particularly limited. The Cr element (B) other than hexavalent Cr in the chemical conversion film may be a trivalent chromium compound (b) contained in the chemical conversion treatment liquid for aluminum-based metallic materials described below that is directly incorporated into the chemical conversion film, or the trivalent chromium compound (b) may be converted into another compound form (such as an oxide) by a chemical conversion reaction with the aluminum-based metallic material and then incorporated.
[0019] The chemical conversion coating according to one embodiment of the present invention may contain hexavalent Cr as long as the intended effect of the present invention is not lost. However, taking into account the impact on the environment, it is preferable that it does not contain hexavalent Cr.
[0020] (C element) The chemical conversion coating according to one embodiment of the present invention contains C (carbon). The content of C in the chemical conversion coating is 6 to 100 mg / m 2 and preferably 10 to 100 mg / m 2 and more preferably 15 to 100 mg / m 2 and even more preferably 20 to 100 mg / m 2 The carbon element content is 6 mg / m 2 If it is lower than this, sufficient corrosion resistance cannot be obtained, and 100 mg / m 2 If it is higher, the cost increases.
[0021] The origin of the C element is not particularly limited, but it is preferably derived from a polymer (C) having a carbonyl group. The polymer (C) having a carbonyl group is not particularly limited as long as it has a carbonyl group in its structure. More specifically, functional groups having a carbonyl group include amide groups, urethane groups, carboxy groups, acrylic groups, ester groups, etc. Examples of the polymer (C) having a carbonyl group include polyester, polyacrylamide, polyurethane, polyacrylic acid, polyacrylic acid ester, etc. Only one type of polymer (C) having a carbonyl group may be contained in the chemical conversion coating, or two or more types may be contained.
[0022] The polymer (C) having a carbonyl group in the chemical conversion coating according to one embodiment of the present invention may be the polymer (C) having a carbonyl group contained in the chemical conversion treatment liquid for aluminum-based metallic materials described below that is directly incorporated into the chemical conversion coating, or the polymer (C) having a carbonyl group may form a complex with a metal compound and a chromium compound in the chemical conversion treatment liquid for aluminum-based metallic materials, and may be co-deposited with the metal compound and the chromium compound by coming into contact with the aluminum-based metallic material.
[0023] Corrosion resistance can be improved by appropriately adjusting the mass ratio (A / B) of the metal element (A) to the Cr element (B) that is not hexavalent Cr. Specifically, the mass ratio (A / B) of the metal element (A) to the Cr element (B) that is not hexavalent Cr is preferably 1.45 to 5.0, more preferably 1.45 to 4.2, and even more preferably 1.45 to 3.64. When two or more kinds of metal elements (A) are contained in the chemical conversion coating, A / B is calculated based on the total content thereof.
[0024] Corrosion resistance can be improved by appropriately adjusting the mass ratio (C / B) of C element to non-hexavalent Cr element (B). Specifically, the mass ratio (C / B) of C element to non-hexavalent Cr element (B) is preferably 0.15 to 7.2, more preferably 0.5 to 7.2, and even more preferably 1.35 to 7.2.
[0025] The chemical conversion coating according to one embodiment of the present invention contains F (fluorine). The presence of F element can be confirmed by fluorescent X-ray analysis. The presence of F (fluorine) element in the chemical conversion coating is desirable from the viewpoint of corrosion resistance.
[0026] The thickness of the chemical conversion coating according to one embodiment of the present invention is not particularly limited, but is preferably 10 to 600 nm, and more preferably 30 to 600 nm.
[0027] In the chemical conversion coating according to one embodiment of the present invention, so long as each of the above-mentioned coating components is contained in a predetermined amount, there are no particular limitations on the distribution of each coating component in the depth direction of the coating. However, in a depth direction emission intensity analysis using a Marcus-type high-frequency glow discharge optical emission surface analyzer (GD-OES), it is desirable for the C element and the O element to be concentrated on the surface layer side, and at least one, preferably two or more elements selected from the group consisting of a metal element (A) and a Cr element (B) that is not hexavalent Cr to be concentrated on the substrate side (hereinafter referred to as the "gradient structure of the chemical conversion coating"), in order to improve corrosion resistance compared to a case where this is not the case.
[0028] Here, the "surface side" refers to a depth range within 20 nm from the outermost surface of the chemical conversion coating in the emission intensity profile of each element obtained by performing a depth direction analysis using a Marcus type high frequency glow discharge optical emission surface analyzer (GD-OES), the "substrate side" refers to a depth range from the depth where the Al intensity first reaches 5 times the average value of the Al intensity in the depth range from the outermost surface of the chemical conversion coating to 5 nm measured by GD-OES, and the "enriched" refers to a position where the intensity of each coating component measured by GD-OES shows a maximum value in the measurement range. FIG. 1 shows an example of an emission intensity profile of each element obtained by performing a depth direction analysis using GD-OES. In this specification, the depth measured by GD-OES is a value converted based on the sputtering rate of Si. Specifically, sputtering conditions that give a sputtering rate of 40 nm / s for Si are determined in advance, and a depth direction analysis using GD-OES is performed under the sputtering conditions, and the sputtering time is converted into a depth.
[0029] The gradient structure of the chemical conversion coating is formed, for example, by contacting an aluminum-based metal material with a chemical conversion treatment liquid for aluminum-based metal materials, which contains at least one metal compound (a) selected from the group consisting of zirconium compounds, titanium compounds, and vanadium compounds, a trivalent chromium compound (b), a polymer having a carbonyl group (C), and a fluorine-containing compound (D), for 60 seconds or more, and then rinsing the aluminum-based metal material with water.
[0030] <<2. Chemical conversion treatment solution for aluminum-based metal materials>> (At least one metal compound (a) selected from the group consisting of zirconium compounds, titanium compounds, and vanadium compounds) The chemical conversion treatment liquid for aluminum-based metallic materials according to one embodiment of the present invention contains at least one metal compound (a) selected from the group consisting of zirconium compounds, titanium compounds, and vanadium compounds. The metal compound (a) may be used alone or in combination of two or more kinds.
[0031] Examples of the zirconium compound include zirconium tetrapropoxide, hexafluorozirconium acid, zirconium nitrate, zirconyl nitrate, zirconium carbonate, zirconium hydroxide, and zirconium oxide. The zirconium compound may be present in the form of zirconium ions in the chemical conversion treatment liquid for aluminum-based metal materials. Examples of the zirconium ions include metal ions of zirconium, complex ions containing zirconium, and oxide ions of zirconium. Examples of the complex ions containing zirconium include hexafluorozirconium ammonium, tetrafluorozirconium, trifluorozirconium ammonium, and hexafluorozirconium salts.
[0032] Examples of titanium compounds include titanium tetrapropoxide, hexafluorotitanium acid, titanium nitrate, titanium carbonate, dititanium hydroxide, and titanium oxide. The titanium compound may be present in the form of titanium ions in the aluminum-based metal material chemical conversion treatment liquid. Examples of titanium ions include titanium metal ions, titanium-containing complex ions, and titanium oxide ions. Examples of titanium-containing complex ions include hexafluorotitanium ammonium, hexafluorotitanium salts, tetrafluorotitanium, and trifluorotitanium ammonium.
[0033] Examples of vanadium compounds include vanadium oxypropoxide, vanadium nitrate, vanadium carbonate, vanadium hydroxide, and vanadium oxide. The vanadium compound may be present in the form of vanadium ions in the aluminum-based metal material chemical conversion treatment liquid. Examples of vanadium ions include vanadium metal ions, vanadium-containing complex ions, and vanadium oxide ions. Examples of vanadium-containing complex ions include vanadium fluoride and hexafluorovanadic acid.
[0034] The content of the metal compound (a) in the chemical conversion treatment liquid for aluminum-based metallic materials according to one embodiment of the present invention is not particularly limited, but is usually 1.5 to 500 mg / L, and more preferably 25 to 300 mg / L, calculated as the value of the metal element zirconium, titanium or vanadium. When two or more kinds of metal compounds (a) are used, the total content of the metal element zirconium, titanium or vanadium contained in each metal compound (a) is defined as the content of the metal compound (a).
[0035] (Trivalent chromium compounds (b)) The chemical conversion treatment liquid for aluminum-based metallic materials according to one embodiment of the present invention contains a trivalent chromium compound (b). Examples of trivalent chromium compounds include chromium fluoride (III), chromium nitrate (III), chromium sulfate (III), chromium oxysulfate (III), and chromium phosphate (III). The trivalent chromium compound may be present in the form of chromium ions in the chemical conversion treatment liquid for aluminum-based metallic materials. Only one type of trivalent chromium compound may be used, or two or more types may be used in combination. The content of the trivalent chromium compound in the chemical conversion treatment liquid for aluminum-based metallic materials is not particularly limited, but is usually 1 to 200 mg / L, and more preferably 25 to 150 mg / L, calculated as a value equivalent to chromium. When two or more types of trivalent chromium compounds are used, the total content of the trivalent chromium compounds is taken as the content of the trivalent chromium compound.
[0036] (Polymer (C) Having Carbonyl Groups) The chemical conversion treatment liquid for aluminum-based metallic materials according to one embodiment of the present invention contains a polymer (C) having a carbonyl group. As described above, the polymer (C) having a carbonyl group is not particularly limited as long as it has a carbonyl group in its structure. More specifically, examples of functional groups having a carbonyl group include an amide group, a urethane group, a carboxy group, an acrylic group, and an ester group. The polymer (C) having a carbonyl group may have only one type of carbonyl group in its structure, or may have two or more types of carbonyl groups. Examples of the polymer (C) having a carbonyl group include polyester, polyacrylamide, polyurethane, polyacrylic acid, and polyacrylic acid ester. The polymer (C) having a carbonyl group may be used alone or in combination of two or more types. The content of the polymer (C) having a carbonyl group in the chemical conversion treatment liquid for aluminum-based metallic materials is not particularly limited, but is usually 1 to 1000 mg / L, and more preferably 100 to 600 mg / L, in terms of carbon. When two or more kinds of polymers (C) having a carbonyl group are used, the total content of the polymers (C) having a carbonyl group is regarded as the content of the polymer (C) having a carbonyl group.
[0037] (Fluorine-containing compound (D)) The aluminum-based metal material chemical conversion treatment liquid according to one embodiment of the present invention contains a fluorine-containing compound (D). Examples of the fluorine-containing compound (D) include hydrofluoric acid, ammonium fluoride, ammonium hydrogen fluoride, germanium fluoride, potassium fluoride, potassium hydrogen fluoride, iron fluoride, hydrosilicic acid, sodium fluoride, sodium hydrogen fluoride, hexafluorozirconium acid, hexafluorotitanium acid, and chromium (III) fluoride. Compounds that fall under both the metal compound (a) or the trivalent chromium compound (b) and the fluorine-containing compound (D) (e.g., hexafluorozirconium acid, hexafluorotitanium acid, and chromium (III) fluoride) function as the respective compounds. Only one type of fluorine-containing compound may be used, or two or more types may be used in combination. The content of the fluorine-containing compound in the chemical conversion treatment solution for aluminum-based metallic materials is not particularly limited, but the free fluorine ion concentration in the entire chemical conversion treatment solution for aluminum-based metallic materials is usually 3 to 100 mg / L, and more preferably 5 to 70 mg / L. The free fluorine ion concentration can be measured using a commercially available fluorine ion meter {ion electrode: fluoride ion composite electrode F-2021 (manufactured by DKK-TOA Corporation)} or the like.
[0038] The pH of the chemical conversion treatment solution for aluminum-based metallic materials according to one embodiment of the present invention is not particularly limited, but is preferably 2.3 to 5.0, and more preferably 3.0 to 4.5. The pH can be adjusted by adding an acid or alkali (e.g., sodium hydroxide, ammonia, ammonium bicarbonate, nitric acid, sulfuric acid, hydrochloric acid, hydrofluoric acid, etc.). Here, the pH in this specification means the value at 25°C. The pH can be measured, for example, with a portable electrical conductivity / pH meter {WM-32EP (manufactured by DKK-TOA Corporation)} or the like.
[0039] In the chemical conversion treatment solution for aluminum-based metallic materials according to one embodiment of the present invention, the corrosion resistance can be improved by appropriately adjusting the mass ratio (A / B) of the metal element (A) to the Cr element (B) that is not hexavalent Cr. Specifically, A / B is preferably 0.6 to 7.0, more preferably 0.6 to 4.2, and even more preferably 0.6 to 1.67. When two or more kinds of metal elements (A) are contained in the chemical conversion treatment solution, A / B is calculated based on their total contents.
[0040] In the chemical conversion treatment solution for aluminum-based metallic materials according to one embodiment of the present invention, the corrosion resistance can be improved by appropriately adjusting the mass ratio (C / B) of C element to non-hexavalent Cr element (B). Specifically, C / B is preferably 0.5 to 20, more preferably 0.5 to 7.2, and even more preferably 0.5 to 3.33.
[0041] In the chemical conversion treatment solution for aluminum-based metallic materials according to one embodiment of the present invention, the corrosion resistance can be improved by appropriately adjusting the mass ratio (X / Y) of the mass (X) of the polymer (C) having a carbonyl group to the total mass (Y) of Zr, Ti, V and Cr. Specifically, X / Y is preferably 0.50 to 2.80, more preferably 0.50 to 1.76, and even more preferably 0.50 to 1.25.
[0042] <<3. Surface treatment method for aluminum-based metal materials>> An aluminum-based metal material with a chemical conversion coating according to one embodiment of the present invention can be obtained by a surface treatment method including a step (i) of contacting an aluminum-based metal material with a chemical conversion treatment solution for aluminum-based metal materials for 60 seconds or more (hereinafter referred to as the "chemical conversion treatment step"), and a step (ii) of washing the aluminum-based metal material with water (hereinafter referred to as the "water washing treatment step") after the step (i). The contact method is not particularly limited, and for example, a dipping treatment method, a spraying treatment method, a pouring treatment method, or a combination of these methods can be used.
[0043] In the chemical conversion treatment step, the temperature of the chemical conversion treatment solution for aluminum-based metallic materials during the contact is preferably within a range of 30°C to 70°C. The contact time is preferably within a range of 60 to 600 seconds, more preferably within a range of 60 to 300 seconds, and even more preferably within a range of 120 to 180 seconds. After the chemical conversion treatment step, a water washing treatment step is carried out. After the chemical conversion treatment step or the water washing treatment step following the chemical conversion treatment step, a drying step may be carried out. For example, drying can be carried out for 10 to 6000 seconds in an atmosphere of 30 to 250°C.
[0044] Prior to the chemical conversion treatment step, although not essential, degreasing, hot water washing, pickling, solvent washing, etc. are usually performed in appropriate combination to remove oil and dirt adhering to the aluminum-based metal material (hereinafter referred to as "cleaning step"). The method of the degreasing is not particularly limited, and can be appropriately selected from methods conventionally used for degreasing of aluminum-based metal materials. Examples of the degreasing method that can be used include solvent degreasing (solvent washing method, solvent vapor cleaning method), alkaline degreasing, electrolytic alkaline degreasing, emulsion degreasing, etc. The aluminum-based metal material that has been subjected to the cleaning step may be subjected to a water washing step before the chemical conversion treatment step.
[0045] In addition, when an aluminum-based metal material having a surface treatment film on the chemical conversion film produced by the method for producing an aluminum-based metal material with a chemical conversion film according to one embodiment of the present invention is produced, a step for forming the surface treatment film may be carried out after the production of the chemical conversion film. This step may be carried out multiple times to form one or more surface treatment films. Furthermore, after the above-mentioned chemical conversion treatment step and before the step for forming the surface treatment film is carried out, one or more water washing steps may be carried out. When the water washing step is carried out, a drying step for drying the surface of the metal material may be carried out thereafter.
[0046] The process for forming the surface treatment film is carried out on the surface of the metal material having the chemical conversion film by using a surface treatment agent or paint. The treatment method is not particularly limited, and a conventionally known method such as immersion, curtain flow coating, airless spray coating, hot spray coating, rolling coating, electrodeposition coating (e.g., cationic electrodeposition coating, anionic electrodeposition coating, etc.), electrostatic (powder) coating, roller coating, brush coating, bar coating, fluidized bed immersion method, etc. can be applied, and a baking process or drying process may be carried out after the treatment as necessary.
[0047] When an aluminum-based metal material having a surface treatment film on the chemical conversion film produced by the method for producing an aluminum-based material with a chemical conversion film according to one embodiment of the present invention is produced, a surface treatment agent may be applied for the purpose of imparting hydrophilicity or the like. The surface treatment agent has a resin. The resin is not particularly limited, but examples thereof include urethane resin, polyvinyl alcohol resin, polyamide resin, epoxy resin, acrylic resin, amine resin, phenol resin, polyvinylpyrrolidone resin, polycarbodiimide resin, and the like. The resin may be a homopolymer of these resins (including modified products in which the side chains of the homopolymers are modified with other compounds), or a copolymer obtained by combining and polymerizing two or more monomers for obtaining these resins or modified products. Of these, it is preferable to use a resin having at least one functional group selected from an amino group, an amide group, a carboxy group, and a hydroxy group. The resin may have only one type of these functional groups, or may have two or more types. The surface treatment agent may contain only one type of resin, or may contain two or more types of resins. The surface treatment agent may contain, in addition to the resin, deionized water, a water-miscible solvent, and the like, as appropriate.
[0048] The applications of the aluminum-based metal material with a chemical conversion coating according to one embodiment of the present invention are not particularly limited, but may be used, for example, in heat exchangers, building materials, automobile parts, battery materials, and the like.
[0049] By carrying out the above treatment, an aluminum-based metal material with a chemical conversion coating or an aluminum-based metal material having a surface treatment coating thereon can be obtained. The suitable thickness of the coating is as described above. The surface treatment coating on the chemical conversion coating may be composed of a single layer, or may be composed of multiple layers by carrying out the above treatment multiple times. EXAMPLES
[0050] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.
[0051] (1. Raw materials used in the preparation of surface treatment agents for aluminum-based metal materials) As shown in Table 1, raw materials A1 to A5 were used as metal compounds (a), raw materials B1 to B3 were used as trivalent chromium compounds (b), raw materials C1 to C4 were used as polymers having a carbonyl group (C), and raw material D1 was used as a fluorine-containing compound (D).
[0052] [Table 1]
[0053] (2. Surface treatment agents for aluminum-based metal materials) The raw materials shown in Table 1 were mixed with water to give the concentrations shown in Table 2, to obtain surface treatment agents 1 to 23 for aluminum-based metallic materials.
[0054] In addition, the content (Y1) of the metal compound (a) shown in Table 2 is a mass concentration converted into metal, the content (Y3) of the trivalent chromium compound (b) is a mass concentration converted into chromium, and the content (X) of the polymer (C) having a carbonyl group is the mass concentration of the polymer itself.
[0055] <Measurement of free fluoride ion concentration> The free fluorine ion concentration in each surface treatment agent for aluminum-based metal materials was measured using a commercially available fluorine ion meter {ion electrode: fluoride ion composite electrode F-2021 (manufactured by DKK-TOA Corporation)}. The results are shown in Table 2.
[0056] [Table 2]
[0057] (3. Surface treatment of aluminum-based metal materials) <Example 1 (chemical conversion treatment)> A 70mm x 75mm x 0.8mmt flat pure aluminum material (A1050P as specified in JIS H 4000:2014) was immersed for 3 minutes in an alkaline degreasing agent (a 20g / L aqueous solution of Fine Cleaner 315E manufactured by Nippon Parkerizing) heated to 60°C, and then the surface was rinsed and cleaned with deionized water. The cleaned pure aluminum material was then immersed for 60 seconds in a surface treatment agent 1 at a temperature of 53°C, which had been adjusted to pH 3.7 using ammonia water. The pure aluminum material was then removed from the surface treatment agent 1 and washed with deionized water, and then dried in an electric oven (80°C for 5 minutes) to obtain an aluminum-based metal material with a chemical conversion coating.
[0058] <Examples 2 to 17 and Comparative Examples 1 to 6 (chemical conversion treatment)> Chemical conversion treatment was carried out under the same conditions as in Example 1 except that the conditions were changed to those shown in Table 3, to obtain aluminum-based metallic materials with chemical conversion coatings of Examples 2 to 17 and Comparative Examples 1 to 6.
[0059] <Comparative Examples 7 to 9 (Painting)> The pure aluminum materials shown in Table 3, which had been cleaned under the same conditions as in Example 1, were immersed in surface treatment agent 12, 16 or 23 at room temperature (about 25°C) for 20 seconds, and then, without rinsing with water, the pure aluminum materials were taken out of surface treatment agent 12, 16 or 23, respectively, and baked and dried in an electric oven (at 150°C for 6 minutes). In this way, aluminum-based metal materials with coatings of Comparative Examples 7 to 9 were obtained.
[0060] [Table 3]
[0061] (4. Analysis of surface-treated aluminum materials) The mass of metal and the mass of carbon per unit area contained in the coating of the surface-treated aluminum materials of Examples 1 to 17 and Comparative Examples 1 to 9 were measured by the following method. The measurement results are shown in Table 4.
[0062] In addition, the concentrated position (surface layer side or substrate side) in the coating thickness direction of each element contained in the surface-treated aluminum materials of Examples 1 to 17 and Comparative Examples 1 to 9 was measured by the following method. The measurement results are shown in Table 4. Note that there were cases where the elements were concentrated in a position between the surface layer side and the substrate side, and not all elements were concentrated on either the surface layer side or the substrate side.
[0063] Furthermore, the presence or absence of carbonyl groups in the molecular structures of the polymers in the surface-treated aluminum materials of Examples 1 to 17 and Comparative Examples 1 to 9 was measured by the following method. The measurement results are shown in Table 4.
[0064] The presence or absence of F element was measured by the following method for the coatings of the surface-treated aluminum materials of Examples 1 to 17 and Comparative Examples 1 to 9. The measurement results are shown in Table 4.
[0065] Furthermore, the presence or absence of hexavalent chromium was measured by the following method for the surface-treated aluminum materials of Examples 1 to 17 and Comparative Examples 1 to 9. The measurement results are shown in Table 4.
[0066] Furthermore, the thickness of the coating was measured by the following method for the surface-treated aluminum materials of Examples 1 to 17 and Comparative Examples 1 to 9. The measurement results are shown in Table 4.
[0067] <Mass of metal per unit area> The mass of metals per unit area (Zr, V, Ti, Cr) was measured using a scanning X-ray fluorescence analyzer {ZSX primus II (Rigaku Corporation)} based on a calibration curve that was created by changing the content of each metal in the film. The measured metal mass was calculated based on the area of X-ray irradiation (π × 15 × 15 mm 2 The diameter of the X-ray irradiation was 30 mmφ. The surface-treated aluminum material was cut into 3.2 cm square pieces to be used as analysis samples, and the average value of three samples was used as the measurement value.
[0068] <Carbon mass per unit area> The carbon equivalent mass per unit area was calculated by using a total organic carbon meter (TOC-L (Shimadzu Corporation)) equipped with a solid sample combustion device to completely combust the organic matter contained in the surface-treated aluminum material at a furnace temperature of 700°C, measuring the carbon mass from a calibration curve prepared in advance using a standard sample, and dividing the measured carbon mass by the surface area (projected area) of the surface-treated aluminum material used in the measurement. The surface-treated aluminum material was cut into pieces of 7.5 mmφ to serve as the analysis sample, and the average value of five samples was used as the measurement value.
[0069] <Presence or absence of carbonyl group> A variable angle reflection accessory was attached to a Fourier transform infrared spectrophotometer (FT-IR) {Spectrum Two (PerkinElmer)} and measurements were taken using the reflection method. The measurement was performed at an infrared light incidence angle of 45° and a resolution of 4 cm. -1 , 32 accumulations, wavenumber range 400-4000cm -1 The infrared absorption spectrum obtained showed an absorption peak (2000 to 1500 cm) derived from a carbonyl group. -1 ) was confirmed. Taking into consideration the variation depending on the measurement location, the presence or absence of carbonyl groups was evaluated based on the results obtained from three randomly selected points on the surface-treated aluminum material. At this time, if a carbonyl group peak was confirmed at two or more of the three measurement points, the carbonyl group was deemed to be "present."
[0070] <Analysis of the gradient structure of the film> The emission intensity analysis of each element was carried out using a Marcus-type high-frequency glow discharge optical emission surface analyzer (GD-OES), JY-5000RF, manufactured by Horiba, Ltd. The GD-OES analysis was performed by argon sputtering in pulse sputtering mode with a measurement range of 10 mmφ. The measurement was started from the outermost surface of the surface-treated aluminum material, and measurements were made every 0.8 nm from the outermost surface toward the aluminum material, which is the base material, to a depth of 2.5 mm. The depth range from the outermost surface of the chemical conversion coating to 20 nm in the depth direction was defined as the "surface side," and the depth range from the outermost surface to 5 nm in the depth direction where the Al intensity first reaches 5 times the average value of the Al intensity in the depth range from the outermost surface to the "base material side," and the position where the intensity of each coating component was maximum (concentrated) in the measurement range was investigated. Considering the variation depending on the measurement location, the gradient structure was evaluated based on the analysis results of three randomly selected points on the surface-treated aluminum material. At this time, it was confirmed that a similar gradient structure was obtained at two or more points out of the three points.
[0071] <Analysis of fluorine in coating> Using a scanning X-ray fluorescence analyzer {ZSX primus II (Rigaku Corporation)}, we investigated whether or not F element was detected in the coating of the surface-treated aluminum material by adjusting the wavelength range in which the fluorescent X-rays of elements Be to U can be detected. The tube used was Rh, and the X-ray irradiation area of the analysis sample was 30 mmφ. The surface-treated aluminum material was cut into 3.2 cm square pieces and used as the analysis sample, and three samples were analyzed. At this time, if fluorine peaks were confirmed at two or more measurement points out of the three points, it was considered fluorine "detected", and if not, it was considered fluorine "not detected".
[0072] <Analysis of hexavalent chromium> A hexavalent chromium elution test was conducted using the diphenylcarbazide coloring method in accordance with JIS H8625-1993 to confirm whether hexavalent chromium was detected in surface-treated aluminum materials. As a result, hexavalent chromium was deemed "detected" when it was 0.05 mg / L or more, and hexavalent chromium was deemed "not detected" when it was less than 0.05 mg / L.
[0073] <Film thickness> The thickness was measured from the results of GD-OES analysis. The thickness was calculated by multiplying the sputtering time (seconds) at which the Al intensity first reached 10 times the average value of the Al intensity in the depth range of 5 nm from the outermost surface by the sputtering rate of Si (40 nm / second).
[0074] (5. Corrosion resistance test for surface-treated aluminum materials) <Corrosion resistance in neutral environments (salt spray test)> A neutral salt spray test (JIS-Z2371:2015) was conducted on the surface-treated aluminum materials of Examples 1 to 17 and Comparative Examples 1 to 9. The evaluation time was 720 hours. After drying, the proportion of white rust that had developed on the surface of the surface-treated aluminum material was measured visually. The proportion of white rust is the proportion of the area where white rust has developed relative to the area of the observed portion. The evaluation criteria are as follows. The evaluation results are shown in Table 4. <Evaluation criteria> 5. White rust percentage: 10% or less 4. White rust percentage: 10% to 30% 3. White rust ratio: 30% to 50% 2. White rust ratio: 50% to 70% 1. White rust rate: over 70%
[0075] <Corrosion resistance in acidic environments [SWAAT test (Sea Water Acidified Test)]> The surface-treated aluminum materials of Examples 1 to 17 and Comparative Examples 1 to 9 were subjected to a SWAAT test (ASTM G85 Annex2). The number of evaluation cycles was 240. After drying, the proportion of white rust that had developed on the surface of the surface-treated aluminum material was measured by visual inspection. The proportion of white rust is the proportion of the area where white rust has developed to the area of the observed portion. The evaluation criteria are as follows. The evaluation results are shown in Table 4. <Evaluation criteria> 5. White rust percentage: 10% or less 4. White rust percentage: 10% to 30% 3. White rust ratio: 30% to 50% 2. White rust ratio: 50% to 70% 1 Ratio of white rust exceeding 70%
[0076] <Corrosion resistance in an acidic environment containing Cu (CAST test)> The CAST test (JIS-Z2371:2015) was conducted on the surface-treated aluminum materials of Examples 1 to 17 and Comparative Examples 1 to 9. The evaluation time was set to 24 hours. After drying, the ratio of white rust generated on the surface of the surface-treated aluminum material was visually measured. The ratio of white rust is the ratio of the area where white rust occurred to the area of the observation site. The evaluation criteria are as follows. The evaluation results are shown in Table 4. <Evaluation criteria> 5 Ratio of white rust 10% or less 4 Ratio of white rust exceeding 10% to 30% or less 3 Ratio of white rust exceeding 30% to 50% or less 2 Ratio of white rust exceeding 50% to 70% or less 1 Ratio of white rust exceeding 70%
[0077]
Table 4
[0078] As described above, the present invention has been described in detail with reference to specific examples. However, it is obvious to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention.
Claims
1. At least one metal element (A) selected from the group consisting of Zr, Ti and V is applied to the surface of an aluminum-based metallic material at a concentration of 1 mg / m 2 ~160mg / m 2 and 5 to 50 mg / m of non-hexavalent Cr element (B). 2 and C element is 6 to 100 mg / m 2 and wherein a mass ratio (A / B) of the metal element (A) to the Cr element (B) that is not hexavalent Cr is 1.45 to 5.0, and a mass ratio (C / B) of the C element to the Cr element (B) that is not hexavalent Cr is 0.15 to 7.
2.
2. 2. The aluminum-based metallic material with a chemical conversion coating according to claim 1, wherein the C element of the chemical conversion coating is derived from a polymer having a carbonyl group.
3. 3. The aluminum-based metallic material with a chemical conversion coating according to claim 1, further comprising an F element in the chemical conversion coating.
4. In the emission intensity analysis using a Marcus-type high-frequency glow discharge optical emission surface analyzer (GD-OES), the depth range within 20 nm from the outermost surface is defined as the surface side, and the depth range beyond the depth at which the Al intensity first reaches 5 times the average value of the Al intensity in the depth range from the outermost surface to 5 nm is defined as the substrate side.
3. The aluminum-based metal material with a chemical conversion coating according to claim 1 or 2, wherein the C element and the O element show maximum strength on the surface layer side, and at least one element selected from the metal element (A) and the Cr element (B) that is not hexavalent Cr shows maximum strength on the substrate side.
5. A chemical conversion treatment liquid for an aluminum-based metallic material, comprising: at least one metal compound (a) selected from the group consisting of zirconium compounds, titanium compounds, and vanadium compounds; a trivalent chromium compound (b); a polymer (C) having a carbonyl group; and a fluorine-containing compound (D).
6. 6. The chemical conversion treatment solution for aluminum-based metallic materials according to claim 5, wherein a mass ratio (A / B) of at least one metal element (A) selected from the group consisting of Zr, Ti and V to a Cr element (B) that is not hexavalent Cr is 0.6 to 7.0, and a mass ratio (C / B) of a C element to the Cr element (B) that is not hexavalent Cr is 0.5 to 20.
7. 7. The chemical conversion treatment solution for aluminum-based metallic materials according to claim 5, wherein a mass ratio (X / Y) of the mass (X) of the polymer (C) having a carbonyl group to the total mass (Y) of Zr, Ti, V and Cr is 0.50 to 2.
80.
8. A step (i) of contacting an aluminum-based metallic material with the chemical conversion treatment solution for an aluminum-based metallic material according to claim 5 or 6 for 60 seconds or more; After the step (i), a step (ii) of washing the aluminum-based metallic material with water; The surface treatment method of the aluminum-based metal material includes the steps of:
9. 9. The method for surface treatment of an aluminum-based metallic material according to claim 8, wherein in the step (i), the time for contacting the aluminum-based metallic material with the chemical conversion treatment solution for aluminum-based metallic materials is 60 to 600 seconds.
Citation Information
Patent Citations
Non-chromate chemical conversion treatment liquid for aluminum alloy, and aluminum alloy chemical conversion treatment method by the same
JP2006316334A
Liquid and method for chemical conversion liquid of metal
JP2006328501A
Metallic material surface treatment agent, metallic material having surface treatment coating, and manufacturing method therefor
WO2019131436A1